Assessing Latin America’s Progress Toward Achieving Universal Health Coverage - Wagstaff, Adam; Dmytraczenko, Tania; Almeida, Gisele; Buisman, Leander R.; Eozenou, Patrick Hoang-Vu; Bredenkamp, Caryn; Cercone, James; Díaz, Yadira; Maceira, Daniel; Molina, Silvia; Mori Sarti, Flávia; Paraje, Guillermo; et al. (Project HOPE, 2015)
Two commonly used metrics for assessing progress toward universal health coverage involve assessing citizens’ rights to health care and counting the number of people who are in a financial protection scheme that safeguards them from high health care payments. On these metrics most countries in Latin America have already “reached” universal health coverage. Neither metric indicates, however, whether a country has achieved universal health coverage in the now commonly accepted sense of the term: that everyone—irrespective of their ability to pay—gets the health services they need without suffering undue financial hardship. We operationalized a framework proposed by the World Bank and the World Health Organization to monitor progress under this definition and then constructed an overall index of universal health coverage achievement. We applied the approach using data from 112 household surveys from 1990 to 2013 for all twenty Latin American countries. No country has achieved a perfect universal health coverage score, but some countries (including those with more integrated health systems) fare better than others. All countries except one improved in overall universal health coverage over the time period analyzed.